Phase-resolved real-time breath analysis during exercise by means of smart processing of PTR-MS data - Schwoebel, Henny; Schubert, Roland; Sklorz, Martin; Kischkel, Sabine; Zimmermann, Ralf; Schubert, Jochen K.; Miekisch, Wolfram (Analytical and bioanalytical chemistry, 2011)
Separation of inspiratory, mixed expired and alveolar air is indispensable for reliable analysis of VOC breath biomarkers. Time resolution of direct mass spectrometers often is not sufficient to reliably resolve the phases of a breathing cycle. To realise fast on-line breath monitoring by means of direct MS utilising low-fragmentation soft ionisation, a data processing algorithm was developed to identify inspiratory and alveolar phases from MS data without any additional equipment. To test the algorithm selected breath biomarkers (acetone, isoprene, acetaldehyde and hexanal) were determined by means of quadrupole proton transfer reaction mass spectrometry (PTR-MS) in seven healthy volunteers during exercise on a stationary bicycle. The results were compared to an off-line reference method consisting of controlled alveolar breath sampling in Tedlar® bags, preconcentration by solid-phase micro extraction (SPME), separation and identification by GC-MS. Based on the data processing method, quantitative attribution of biomarkers to inspiratory, alveolar and mixed expiratory phases was possible at any time during the experiment, even under respiratory rates up to 60/min. Alveolar concentrations of the breath markers, measured by PTR-MS ranged from 130 to 2,600 ppb (acetone), 10 to 540 ppb (isoprene), 2 to 31 ppb (acetaldehyde), whereas the concentrations of hexanal were always below the limit of detection (LOD) of 3 ppb. There was good correlation between on-line PTR-MS and SPME-GC-MS measurements during phases with stable physiological parameters but results diverged during rapid changes of heart rate and minute ventilation. This clearly demonstrates the benefits of breath-resolved MS for fast on-line monitoring of exhaled VOCs. Figure Experimental setup showing bicycle ergometer and analytical pathways: Right side PTR-MS: identification of respiratory phases by means of the new algorithm. Left side: confirmation of PTR-MS data for exhaled isoprene by means of GC-MS analysis